Local Neuronal Responses to Intracortical Microstimulation in Rats' Barrel Cortex Are Dependent on Behavioral Context - Butovas, Sergejus; Schwarz, Cornelius (Frontiers in Behavioral Neuroscience, 2022)
The goal of cortical neuroprosthetics is to imprint sensory information as precisely as possible directly into cortical networks. Sensory processing, however, is dependent on the behavioral context. Therefore, a specific behavioral context may alter stimulation effects, and thus, perception. Here we report how passive vs. active touch i.e. the presence or absence of whisker movements affects local field potential (LFP) responses to micro-stimulation in barrel cortex in head-fixed behaving rats trained to move their whiskers voluntarily. The LFP responses to single current pulses consisted in a short negative deflection corresponding to a volley of spike activity followed by a positive deflection lasting ~100 ms, corresponding to a long-lasting suppression of spikes. Active touch had a characteristic effect on this response pattern. While the first phase including the negative peak remained stable, the later parts consisting of the positive peak were considerably suppressed. The stable phase varied systematically with distance of the electrode from the stimulation site, pointing to saturation of neuronal responses to electrical stimulation in an intensity dependent way. The response suppression during active touch was seen as well after cutting the sensory nerve indicating that it corresponds to a central interaction. Our results suggest that modulatory effects known from normal sensory processing affect the response to cortical micro-stimulation as well. The network response to micro-stimulation is highly amenable to the behavioral state and must be considered for future approaches to imprint sensory signals into cortical circuits with neuroprostheses.